Bioassays of cyclic GMP or vitamin E - K. D. MUNKRES (Fungal Genetics Reports, 1990)
Age-1 mutants of Neurospora are conditional auxotrophs responding to cGMP or vitamin E (tocopherol). Feeding those compounds phenotypically cures their short life span and abnormal colony development. Supplement of cGMP also phenotypically cures their antioxienzyme deficiencies (Munkres 1990a Free Radical Bio. Med., in press). An analogous class of Saccharomyces mutants is doubly-deficient in two superoxide dismutase isoenzymes and, consequently, growth is inhibited by various oxidative stresses. Supplements of minute concentrations of cGMP or vitamin E permit those mutants to grow under oxidative stress (Munkres 1990b Free Radical Bio. Med.).